Literacy and education understanding the new literacy studies in the classroom - Pahl, Kate; Rowsell, Jennifer 1969- (SAGE, 2012)
Presenting a comprehensive guide on how to rethink, plan and apply language in the classroom to meet the contemporary needs and skills of elementary students, this text looks at current literary research in order to provide a framework for teachers and students
Previous edition: London: Paul Chapman, 2005
Keywords: Literacy -- Study and teaching (Elementary); Literacy -- Study and teaching (Secondary); Lesenlernen; Unterricht; Didaktik; Einführung